(untitled) (Conferencea, 2022)
According to pediatric gastroenterologists, about 70% of the child population suffers from chronic constipation [1], however, it should be noted that the true frequency of constipation in children remains unclear, since not all cases of diseases are registered due to the low appeal of parents, especially at the initial stage of the disease. Children "outgrow" the problem of constipation, which is not confirmed by long-term observations: 30-52% of children have symptoms that persist for the next 5 years, about 25% of children continue to suffer from constipation in adulthood [2].